2012
DOI: 10.1007/s00421-012-2565-8
|View full text |Cite
|
Sign up to set email alerts
|

Simulated dive in rats lead to acute changes in cerebral blood flow on MRI, but no cerebral injuries to grey or white matter

Abstract: In this study, the effect of a simulated dive on rat brain was investigated using several magnetic resonance imaging (MRI)-methods and immunohistochemistry. Rats were randomly assigned to a dive- or a control group. The dive group was exposed to a simulated air dive to 600 kPa for 45 min. Pulmonary artery was monitored for vascular gas bubbles by ultrasound. MRI was performed 1 h after decompression and at one and 2 weeks after the dive with a different combination of MRI sequences at each time point. Two week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The experiments were conducted on six male Sprague Dawley (SD) rats [ 33 ] weighing 250–300 g. SD rats were widely used in behavior and neuroscience studies due to their docile nature, strong adaptability, and excellent reproductive performance [ 34 , 35 , 36 , 37 ]. Each rat was individually maintained in a plexiglass cage with 12 h light/12 h dark cycles.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments were conducted on six male Sprague Dawley (SD) rats [ 33 ] weighing 250–300 g. SD rats were widely used in behavior and neuroscience studies due to their docile nature, strong adaptability, and excellent reproductive performance [ 34 , 35 , 36 , 37 ]. Each rat was individually maintained in a plexiglass cage with 12 h light/12 h dark cycles.…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore possible that whereas cerebral circulation following a dive may increase (Havnes et al. ), the reduction in spinal arterial blood flow could enhance the formation of arterial bubbles in the spinal cord (Fig. ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous experiments in our laboratory has shown that decompression from heliox saturation at a rate of 1 bar/20 s (fast), resulted in DCS symptoms in approximately 50% of the animals, whereas the slow rate of 1 bar/10 min did not result in DCS or venous gas bubbles [ 14 , 15 ]. Structural MRI did not reveal morphological changes in CNS in rats with severe bubble formation and DCS symptoms after air and heliox dives [ 14 , 16 ]. However, from functional MRI, Havnes et al (2013) concluded that circulatory changes might occur in the brain during the acute phase [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Structural MRI did not reveal morphological changes in CNS in rats with severe bubble formation and DCS symptoms after air and heliox dives [ 14 , 16 ]. However, from functional MRI, Havnes et al (2013) concluded that circulatory changes might occur in the brain during the acute phase [ 16 ]. Increased serum levels of the protein biomarker S100B, predominantly found in brain glial cells, have been associated with brain injury [ 17 ].…”
Section: Introductionmentioning
confidence: 99%